Cost to government health-care services of treating acute self-poisonings in a rural district in Sri Lanka - Kanchana Wickramasinghe; Paul Steele; Andrew Dawson; Dinusha Dharmaratne; Asha Gunawardena; Lalith Senarathna; Dhammika de Siva; Kusal Wijayaweera; Michael Eddleston; Flemming Konradsen (The World Health Organization, 2009)
OBJECTIVE: To estimate the direct financial costs to the Sri Lanka Ministry of Health of treating patients after self-poisoning, particularly from pesticides, in a single district. METHODS: Data on staff, drug, laboratory and other inputs for each patient admitted for self-poisoning were prospectively collected over a one-month period from one general hospital (2005) and five peripheral hospitals (2006) in the Anuradhapura district. Data on transfers to secondary- and tertiary-level facilities were obtained for a 6-month period from 30 peripheral hospitals. The cost of the inputs in United States dollars (US$), using 2005 figures, was derived from hospital accounts. FINDINGS: The average total cost of treating a self-poisoned patient at the general hospital was US$ 31.83, with ward staff input and drugs being the highest expenditure category and only US$ 0.19 of this sum related to capital and maintenance costs. The average total cost of treatment was highest for self-poisoning with pesticides (US$ 49.12). The patients placed in the intensive care unit, who comprised 5% of the total, took up 75% of the overall treatment cost for all self-poisoned patients at the general hospital. The average total cost of treating self-poisoned patients at peripheral hospitals was US$ 3.33. The average patient cost per transfer was US$ 14.03. In 2006, the total cost of treating self-poisoned patients in the Anuradhapura district amounted to US$ 76 599, of which US$ 53 834 were comprised of pesticide self-poisonings. Based on the total treatment cost per self-poisoned patient estimated in this study, the cost of treating self-poisoned patients in all of Sri Lanka in 2004 was estimated at US$ 866 304. CONCLUSION: The cost of treating pesticide self-poisonings may be reduced by promoting the use of less toxic pesticides and possibly by improving case management in primary care hospitals. Additional research is needed to assess if increasing infrastructure and staff at peripheral hospitals could reduce the overall cost to the government, optimize case management and reduce pressure on secondary services.